#### Solve simultaneous linear equations:

(i) (3a – 2b)^{2} + 3(3a – 2b) – 10

(ii) (x^{2} – 3x) (x^{2} – 3x + 7) + 10

**Solution:**

(i) (3a – 2b)^{2} + 3(3a – 2b) – 10

Let us assume, (3a – 2b) = p

p^{2} + 3p – 10

p^{2} + 5p – 2p – 10

Take out common in all terms,

p(p + 5) – 2(p + 5)

(p + 5) (p – 2)

Now, substitute the value of p

(3a – 2b + 5) (3a – 2b – 2)

(ii) (x^{2} – 3x) (x^{2} – 3x + 7) + 10

(x^{2} – 3x) (x^{2} – 3x + 7) + 10

Let us assume, (x^{2} – 3x) = q

q (q + 7) + 10

q^{2} + 7q + 10

q^{2} + 5q + 2q + 10

q(q + 5) + 2(q + 5)

(q + 5) (q + 2)

Now, substitute the value of q

(x^{2} – 3x + 5) (x^{2} – 3x + 2)

**More Solutions:**

- Solve the following systems of simultaneous linear equations.
- Solve the following pairs of linear equations.
- Solve simultaneous linear equations: (i) 2/x + 2/3y = 1/6
- Solve simultaneous linear equations: (i) (7x – 2y)/ xy = 5
- Solve simultaneous linear equations: (i) 3x + 14y = 5xy
- Solve simultaneous linear equations: (i) 20/ (x + 1) + 4/ (y – 1) = 5
- Solve simultaneous linear equations: (i) 1/ 2(2x + 3y) + 12/ 7(3x – 2y) = ½
- If r = 3, y =k is a solution of the equation 3x – 4y +7 = 0
- If x = a, y = b is the solution of the equations x -y = 2 and x + y = 4.